Why Organisms? - Bizzarri, Mariano; Soto, Ana M.; Sonnenschein, Carlos; Longo, Giuseppe (Organisms. Journal of Biological Sciences, 2017)
At the beginning of the 21st century, biology is facing an epistemological crisis which anticipates a paradigm change. Reductionism and the molecular analysis it favors have failed to bring about an understanding of complex phenomena in biology. This will require a reappraisal of old research concepts. The dominant view during the last fifty years has been that development is merely the unfolding of a genetic program. This perception is now being challenged by the resurgence of the once prominent fields of biological inquiry, namely, ecological and evolutionary developmental biology. However, these efforts remain few and far between because they are diluted by a sea of publications still based on reductionist interpretations. Meanwhile, there is no source explicitly committed to a perspective centered on organisms. Thus, there is a need for a journal dedicated to high quality theoretical and experimental work while promoting an interdisciplinary approach to the main topics in biology.